Leaf Area Influences Photosynthetic Activity, Yield, Quality and Juice Recovery in Manjari Medika Grape - Kakade, P. B.; Somkuwar, R. G.; Jadhav, A. S.; Dhemre, J. K.; Nikumbhe, P. H.; Deshmukh, N. A. (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted at ICAR-National Research Centre for Grapes, Pune during October 2023 to March 2024 to assess the leaf area requirement of Manjari Medika grape variety. The variation in leaf above the bunch on a fruit bearing shoot was created such as 10, 12, 14, 16 and >16 leaves. Manjari Medika grapevines grafted on Dogridge rootstock, spaced at 9×5 ft trained to extended Y- trellis was selected for the study. Maximum bunch weight (375.30 g), 50-berry weight (106.49 g), TSS (20.40°B), yield vine-1 (29.20 kg) and juice recovery (70.25%) as well as highest photosynthetic activity such as assimilation rate (14.50 µmol CO2 m-2 s-1) and transpiration rate (2.64 mmol H2O m-2 s-1) and total chlorophyll content (45.25 mg ml-1) was observed in 12 leaves shoot-1 above the bunch while, minimum bunch weight (320.10 g), 50-berry weight (92.55 g), TSS (18.60°B), yield vine-1 (25.60 kg) and juice recovery (65.30%) were observed in 16 leaves above the bunch. However, the leaf area shoot-1 (2760.80 cm2), leaf area vine-1 (69020.00 cm2) and leaf area bunch-1 (878.12 cm2) were found sufficient for quality grape and juice production, which was achieved by maintaining 12 leaves (878.12 cm2) per shoot above the bunch which ensured high-quality grape and juice production in Manjari Medika grape.